Poverty alleviation strategy by small agri-businesses in the rural area of Mal - Azmah Othman, Muhammad Firos Mustaffa, Kuppusamy Singaravelloo, (Opción, 2019)
This paper examines the effectiveness of entrepreneurship development on increasing income and reducing poverty of smallholder farmers in Malaysian via comparative qualitative research methods. As a result, the level of support by members of the smallholder family is also not forthcoming to ensure the success of the entrepreneurship development programmes. Mostly, these smallholder farmers live in rural areas which often lack infrastructure and facilities. In conclusion, perspective and mental changes of the smallholder farmer communities to involve them in different areas of entrepreneurial development will be important to safeguard their wellbeing